What do we know about cognitive functioning in adult congenital heart disease?. (13th June 2013) - Tyagi, Manavi; Austin, Katie; Stygall, Jan; Deanfield, John; Cullen, Shay; Newman, Stanton P.
Abstract: With the advent of improved medical and surgical care in congenital heart disease, there has been an increase in the number of patients who survive into adulthood, giving rise to a new patient population 'Adults with congenital heart disease'. In the past, morbidity and mortality were the primary concerns for this group. However, with improvements in outcome attention has shifted to other factors such as psychosocial and cognitive functioning. This paper reviews the literature on the cognitive functioning in adult congenital heart disease patients. A total of five relevant articles were retrieved via electronic searches of six databases, including MEDLINE, EMBASE, CINAHL, AMED, PsychINFO, and PubMed. The results displayed a consensus on the presence of some cognitive difficulties in adult congenital heart disease patients. The aetiology of cognitive dysfunctions appears to be multifactorial. The literature is limited by the very small number of studies looking at adults with congenital heart disease, with the majority focusing on cognitive functioning among children with congenital heart disease. However, the presence of cognitive dysfunctions and the resulting impact on the patient's day to day lives warrant for a more detailed and prospective research to enhance the understanding of its aetiology and impact.